TheOJA 2019
DOI: 10.21105/astro.1905.06082
|View full text |Cite
|
Sign up to set email alerts
|

Modelling baryonic feedback for survey cosmology

Abstract: Observational cosmology in the next decade will rely on probes of the distribution of matter in the redshift range between 0 < z < 3 to elucidate the nature of dark matter and dark energy. In this redshift range, galaxy formation is known to have a significant impact on observables such as two-point correlations of galaxy shapes and positions, altering their amplitude and scale dependence beyond the expected statistical uncertainty of upcoming experiments at separations under 10 Mpc. Successful extraction of i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
122
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 162 publications
(128 citation statements)
references
References 198 publications
4
122
0
Order By: Relevance
“…Note that this is only expected to be true if galaxies trace the correct haloes in the simulations (i.e., they have the correct stellar mass-halo mass relation, so that the selected galaxies have the correct bias with respect to clustering of matter) and the adopted cosmology is also broadly correct (so that the simulations have the correct matter clustering). The agreement of the predictions of the simulations with the observed galaxy overdensity power spectrum on small scales in particular may at first seem surprising, given the relatively large spread in predictions from hydrodynamical simulations for quantities like the total matter power spectrum at fixed cosmology (e.g., Chisari et al 2019;van Daalen et al 2019). However, it has been shown previously that many of the clustering statistics of galaxies can be reproduced relatively well by simple abundance matching techniques (see Conroy & Wechsler 2009 and references therein).…”
Section: Galaxy Overdensity Power Spectrummentioning
confidence: 94%
“…Note that this is only expected to be true if galaxies trace the correct haloes in the simulations (i.e., they have the correct stellar mass-halo mass relation, so that the selected galaxies have the correct bias with respect to clustering of matter) and the adopted cosmology is also broadly correct (so that the simulations have the correct matter clustering). The agreement of the predictions of the simulations with the observed galaxy overdensity power spectrum on small scales in particular may at first seem surprising, given the relatively large spread in predictions from hydrodynamical simulations for quantities like the total matter power spectrum at fixed cosmology (e.g., Chisari et al 2019;van Daalen et al 2019). However, it has been shown previously that many of the clustering statistics of galaxies can be reproduced relatively well by simple abundance matching techniques (see Conroy & Wechsler 2009 and references therein).…”
Section: Galaxy Overdensity Power Spectrummentioning
confidence: 94%
“…The shape of the power spectrum is strongly affected by baryonic processes on scales k 10 −1 h/Mpc. For 10 −1 < k < 10 h/Mpc, most of the simulations predict a deficit of power with respect to the N-body case, although the actual amplitude of the effect is highly uncertain [324]. The evacuation of baryons from the central regions of galaxy groups under the influence of feedback is responsible for the deficit of power on scales of ∼ 1 Mpc, i.e., roughly the typical size of galaxy groups.…”
Section: Impact On Cosmological Probesmentioning
confidence: 99%
“…Chisari et al [324] showed that numerical simulations have not yet converged on the actual impact of feedback on the power spectrum (see their Figure 3). For instance, the very strong feedback that was implemented in the original Illustris simulation, which was sufficient to completely evacuate the gas content from most groups (see Figure 15), leads to a very strong suppression of power (>30%) on scales of a few hundred kpc.…”
Section: Impact On Cosmological Probesmentioning
confidence: 99%
“…In the discussion above we have purposefully left out the effects of small-scale baryonic physics. This is because the bias expansion is only expected to be valid on scales where these baryonic effects -for example due to AGN feedback or ionizing radiation -are expected to be small (Chisari et al 2019;Borrow et al 2019) and manifest as perturbative corrections ∝ k 2 PL(k) to the power spectrum (Lewandowski et al 2015;Schmidt & Beutler 2017 ( ,s 2 ) ( , 2 ) 10 2 10 1 10 0 z = 1.0 (s 2 ,s 2 ) LPT Figure 1. The 15 'basis' cross-spectra, P ij , at z = 0 (upper panels) and z = 1 (lower panels).…”
Section: The Bias Expansionmentioning
confidence: 99%